Pengaruh Inovasi Layanan dan Kualitas terhadap Keputusan Nasabah Menabung pada PT BPRS Al-Washliyah Medan - Sriana Dewi; Maya Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of service innovation and quality on customers' decisions to save at PT BPRS Al-Washliyah Medan, both partially and simultaneously. This research uses an associative approach. The population taken was all PT BPRS customers, with a total sample of 100 customers taken using the accidental sampling method. The data collection method uses questionnaires by distributing questionnaires, interviews and direct observation. Data analysis in this research uses Multiple Linear Regression Analysis Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00. The results of this research partially show that the service innovation variable has a significant effect on customers' decisions to save at PT BPRS Al-Washliyah Medan. The quality variable has a significant effect on customers' decisions to save at PT BPRS Al-Washliyah Medan. Simultaneously, the variables of service innovation and quality have a significant influence on customers' decisions to save at PT BPRS Al-Washliyah Medan.